2003
DOI: 10.1016/s0020-7292(03)00210-8
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus in pregnancy in an African population

Abstract: Health education and provision of modern affordable methods of management of diagnosed cases such as uristix and hemastix will improve maternal and fetal outcome in pregnant diabetics in Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 9 publications
5
45
1
Order By: Relevance
“…The established incidence of 5.1% for DM in pregnancy in the current study is much higher than previously reported rates of 1.7% [17] and 3% [7] . However, the incidence of pregestational DM in the study (0.8%) is comparable with the 1% incidence reported for the USA [12] , while the incidence of the GDM in our study, 4.3%, is within the range of 1-14% reported for the USA [3] .…”
Section: Discussioncontrasting
confidence: 78%
“…The established incidence of 5.1% for DM in pregnancy in the current study is much higher than previously reported rates of 1.7% [17] and 3% [7] . However, the incidence of pregestational DM in the study (0.8%) is comparable with the 1% incidence reported for the USA [12] , while the incidence of the GDM in our study, 4.3%, is within the range of 1-14% reported for the USA [3] .…”
Section: Discussioncontrasting
confidence: 78%
“…2,24 In a different population, the reported prevalence was approximately 1%. 25 In this retrospective study of antenatal patient population who were selectively screened for GDM, FBS test method identified as much as 9% prevalence, excluding another 8% that could be termed gestational prediabetes. Indeed, it is estimated that prevalence of GDM ranges from 1 to 14%, or average of 7%, depending on method of testing and population.…”
Section: Discussionmentioning
confidence: 95%
“…Delivery by CS was more common in Group A (83.3%) than Group B (61.9%). According to Ozumba et al the overall cesarean section rate was high (36%) among diabetics with previous cesarean section and cephalopelvic disproportion being the commonest indications 30 . There is also increased risk of macrosomia in male infants as compared to female ones.…”
Section: Discussionmentioning
confidence: 99%